Implementation and Effectiveness of Drug Education Program Of Saint Joseph Institute Of Technology - Herrera, Fernando T. (JPAIR Multidisciplinary Research, 2010)
The study endeavoured to determine the level of implementation and level of effectiveness of Drug Education Program (DEP) of Saint Joseph Institute of Technology which shall be the basis for Drug Education Program enhancement in the institution. Results revealed that DEP in the school was fully implemented as evidenced by its inclusion in the curriculum and provision of relevant resources which aimed to nurture, build resilience and wellbeing and support the development of emotional intelligence and social competency of the students. Announcement or publication, trainings among faculty ,information drive through relevant symposium or fora, and monitoring and evaluation were as well highly implemented to enable the students gain awareness and adequate information concerning the ill effects of unlawful drugs. Most of the student respondents admitted that the knowledge they gained out of the Program has nothing to do with changing their behaviour, but they claimed that somehow, the Program has helped them become more aware of the effects of drugs to their behaviour once influenced or enslaved by them.
Keywords: Implementation; effectiveness; Drug Education Program; SJIT